Increased DJ-1 and α-Synuclein in Plasma Neural-Derived Exosomes as Potential Markers for Parkinson’s Disease - Zhao, Zhen-Hua; Chen, Zhi-Ting; Zhou, Rui-Ling; Zhang, Xu; Ye, Qin-Yong; Wang, Yin-Zhou (Frontiers in Aging Neuroscience, 2019)
The diagnosis of PD can be difficult, particularly in early stages. Therefore, the identification of novel biomarkers is imperative for the diagnosis and monitoring disease progression in PD. DJ-1 and a-synuclein, are two proteins that are critically involved in the pathogenesis of PD, and have been examined as disease biomarkers in several recent studies. However, to the best of our knowledge, no study exists regarding DJ-1 in plasma neural-derived exosomes, In the present study, the levels of DJ-1 and α-synuclein in plasma neural-derived exosomes were studied together in order to investigate novel biomarkers for PD. DJ-1 and α-synuclein in plasma and plasma neural-derived exosomes of the patients with PD and controls were quantified by ELISAs. The data revealed that the levels of DJ-1 and α-synuclein in plasma neural-derived exosomes and the ratio of plasma neural-derived exosomal DJ-1 to total DJ-1 were significantly higher in patients with PD, compared with controls, while levels of DJ-1 and α-synuclein in plasma exhibited no difference between the patients with PD and controls. However, no relationship was identified between biomarkers and disease progression. In addition,, significant positive correlations between DJ-1 and α-synuclein in plasma neural-derived exosomes were observed in the patients with and in controls. We hypothesize that DJ-1 in plasma neural-derived exosomes may be used as a potential biomarker as α-synuclein in PD and they might participate in the mechanism of Parkinson’s disease together.